PENGARUH JARAK TANAM TERHADAP PERTUMBUHAN DAN PRODUKTIVITAS TANAMAN BAWANG DAUN SISTEM AEROPONIK - Salsabila, Afifah; Pareira P, Boy Macklin; Ayu S, Yogina Lestari; Kristian S, Wahyu (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2024)
Welsh onion production in Indonesia is increasing along with population growth to meet its needs. Welsh onion are often used as a flavoring ingredient (condiment) for food. However, Indonesia's land for farming is increasingly limited. Increasing the production of leeks can be achieved by cultivating leeks (Allium fistulosum L.) using an aeroponic system which does not require a lot of space. The research method used in this research is an experimental method. The research used three treatments with P1 planting distance of 6 cm, P2 planting distance of 9 cm, and P3 planting distance of 12 cm. Plant growth in the P3 treatment resulted in significantly different plant heights and plant weights compared to the P1 treatment. However, productivity in treatment P1 produced the highest value compared to other treatments